The environmental and macroeconomic effects of socially responsible investment - Lammertjan Dam; Ben J. Heijdra (Center for Economic Studies and ifo Institute (CESifo), 2008)
We analyze the effects of socially responsible investment and public abatement on environmental quality and the economy in a continuous-time dynamic growth model featuring optimizing households and firms. Environmental quality is modelled as a renewable resource. Consumers can invest in government bonds or firm equity. Since investors feel partly responsible for environmental pollution when holding firm equity, they require a premium on the return to equity. We show that socially responsible investment behaviour by households partially offsets the positive effects on environmental quality of public abatement policies.
Keywords: H23; M14; O16; O41; Q21; 330; Socially responsible investment; economic growth; environmental economics; resource dynamics; stock market; Ethische Geldanlage; Kapitalanlage; Umweltbewusstsein; Umweltpolitik; Umweltschutzinvestition; Wirtschaftspolitische Wirkungsanalyse; Umweltschutz; Erneuerbare Ressourcen; Wachstumstheorie; Theorie